Preformulation of FK506 Prodrugs for Improving Solubility - Na, Young-Guk; Jun, Hye-Suk; Kim, Daehee; Park, Byong-Chul; Lim, Si-Kyu; Lee, Ki-Ho; Hwang, Sung-Joo; Park, Jeong-Sook; Jung, Sang-Hun; Cho, Cheong-Weon (Bulletin of the Korean Chemical Society, 2016)
In order to improve water solubility of a lipophilic drug, tacrolimus (FK506), two prodrugs (FK506‐G or FK506‐S) such as FK506‐M32‐LS‐G (FK506‐G) and FK506‐M32‐LS‐SL (FK506‐S) were synthesized. Two prodrugs (FK506‐G or FK506‐S), including FK506, were characterized by differential scanning calorimetry (DSC), X‐ray diffractometry (XRD), scanning electron microscopy (SEM), enzymatic kinetics, and cytotoxicity. A phase solubility test was conducted in distilled water, and the solubility of two prodrugs (FK506‐G or FK506‐S) was measured in various pH values for pH solubility profiles. Most interesting was that FK506‐S showed the highest solubility, 866 μg/mL in water. In vitro enzymatic kinetics of two prodrugs (FK506‐G or FK506‐S) in human plasma was evaluated by measuring the decrease of FK506‐G or FK506‐S as well as the increase of FK506 by HPLC, and FK506‐G or FK506‐S was metabolized in 1 h in human plasma. Two prodrugs (FK506‐G or FK506‐S) including FK506 showed an IC50 of 336.6 μg/mL for FK506, 337.9 μg/mL for FK506‐G, or 480.1 μg/mL for FK506‐S against a conjunctive cell line, Clone 1‐5c‐4 cells. Taken together, FK506‐S could be the most optimal prodrug for aqueous preparations based on preformulation data.